Перехоплення побічних електромагнітних випромінювань персональних комп'ютерів, що використовують цифрові інтерфейси - Санжарова, А. К. (ХНУРЕ, 2025)
This work is devoted to analyzing the threats of intercepting side electromagnetic emissions (SEME) from personal computers that use digital video interfaces. The mechanisms of SEME formation and their impact on the security of displayed information are examined. Special attention is paid to methods of image reconstruction based on intercepted signals and to the factors affecting text readability.
Keywords: перехоплення електромагнітних випромінювань; випромінювання персональних комп'ютерів